Targeted Therapy and Immunotherapy are Novel Treatment Plans of Hepatocellular Carcinoma that is not Amenable to Surgical Resection: Emerging Trends in Combined Treatment Strategies - Gaoxiong Tan; Wenyong Feng; Deren Yang; Jian Pu (International Journal of Biology and Life Sciences, 2026)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality worldwide, with advanced unresectable disease presenting a significant therapeutic challenge. The treatment paradigm has undergone a fundamental transformation, shifting from tyrosine kinase inhibitor (TKI) monotherapy to combination strategies integrating targeted therapy with immunotherapy. Atezolizumab plus bevacizumab, combining programmed cell death ligand 1 (PD-L1) blockade with anti-vascular endothelial growth factor (VEGF) therapy, established itself as the standard first-line regimen following the landmark IMbrave150 trial, with median overall survival of approximately 19.7 months. Durvalumab plus tremelimumab (STRIDE), a dual immune checkpoint inhibitor regimen, has emerged as an alternative first-line option with unprecedented long-term survival data. Emerging combination strategies include PD-1 inhibitors paired with multitargeted TKIs, bispecific antibodies, and novel therapeutic approaches. Network meta-analyses and real-world evidence suggest comparable efficacy among these regimens, with differential safety profiles facilitating individualized treatment selection. However, significant challenges persist, including the lack of reliable predictive biomarkers for patient stratification, with only approximately one-third of patients responding to current regimens. Emerging biomarkers such as circulating tumor DNA dynamics, interferon-γ signaling signatures, imaging-based radiomic features, and machine learning-based prognostic models show promise in predicting treatment response. The optimal integration of combination immunotherapy with locoregional therapies such as transarterial chemoembolization and radiotherapy remains an area of active investigation. This review synthesizes current evidence on targeted therapy combined with immunotherapy for advanced unresectable HCC, emphasizing combination treatment strategies, comparative efficacy, predictive biomarkers, and future research directions to optimize patient outcomes.